Characterizing microbial communities associated with northern root-knot nematode (Meloidogyne hapla) occurrence and soil health - Lartey, Isaac; Benucci, Gian M. N.; Marsh, Terence L.; Bonito, Gregory M.; Melakeberhan, Haddish (Frontiers in Microbiology, 2023)
The northern root-knot nematode (Meloidogyne hapla) causes extensive damage to agricultural crops globally. In addition, M. hapla populations with no known genetic or morphological differences exhibit parasitic variability (PV) or reproductive potential associated with soil type. However, why M. hapla populations from mineral soil with degraded soil health conditions had a higher PV than populations from muck soil is unknown. To improve understanding of soil biophysicochemical conditions in the environment where M. hapla populations exhibited PV, this study characterized the soil microbial community, core-and indicator-species structure associated with M. hapla occurrence and soil health conditions in 15 Michigan mineral and muck vegetable production fields. Bacterial and fungal communities in soils from where nematodes had been isolated were characterized with high throughput sequencing of 16S and Internal Transcribed Spacer (ITS) rDNA. Results showed that, M. hapla-infested, as well as disturbed and degraded muck fields, had lower bacterial diversity (observed richness and Shannon) compared to corresponding mineral soil fields or non-infested mineral fields. Bacterial and fungal community abundance varied by soil group, soil health conditions and/or M. hapla occurrence. A core microbial community was found to consist of 39 bacterial and 44 fungal sub-operational taxonomic units (OTUs) across all fields. In addition, 25 bacteria were resolved as indicator OTUs associated with M. hapla presence or absence, and 1,065 bacteria as indicator OTUs associated with soil health conditions. Out of the 1,065 bacterial OTUs, 73.9% were indicator of the stable, 8.4% of the disturbed, 0.4% of the degraded condition, and no indicators were common to the three categories. Collectively, these results provide a foundation for in-depth understanding of the environment where M. hapla exists and conditions associated with PV.